2016
DOI: 10.1111/sed.12292
|View full text |Cite
|
Sign up to set email alerts
|

Thresholds of intrabed flow and other interactions of turbidity currents with soft muddy substrates

Abstract: Controlled laboratory experiments reveal that the lower part of turbidity currents has the ability to enter fluid mud substrates, if the bed shear stress is higher than the yield stress of the fluid mud and the density of the turbidity current is higher than the density of the substrate. Upon entering the sub-strate, the turbidity current either induces mixing between flow-derived sediment and substrate sediment, or it forms a stable horizontal flow front inside the fluid mud. Such 'intrabed' flow is surrounde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 55 publications
2
8
0
Order By: Relevance
“…-The intraflow turbidity current experiments from Baas et al (2014Baas et al ( , 2016 may also explain the crocodile mouth, and share many features with our observations. In particular, these authors were able to experimentally produce a zone of mixing around the injectite, some nodules at the interface, and the sandwiching of the penetrated layer.…”
Section: Collision and Intraflowssupporting
confidence: 83%
See 1 more Smart Citation
“…-The intraflow turbidity current experiments from Baas et al (2014Baas et al ( , 2016 may also explain the crocodile mouth, and share many features with our observations. In particular, these authors were able to experimentally produce a zone of mixing around the injectite, some nodules at the interface, and the sandwiching of the penetrated layer.…”
Section: Collision and Intraflowssupporting
confidence: 83%
“…Building on the analogue experiments of Verhagen et al (2013), Baas et al (2014Baas et al ( , 2016 enlarged the fields of flow-bed interactions and showed that "the lower part of turbidity currents has the ability to enter fluid mud substrates". They conclude that such "intrabed currents are driven by bed shear stress exceeding the bed cohesive strength, and by flow density exceeding bed density".…”
Section: Intraflow Beds and Bulldozer Effectsmentioning
confidence: 99%
“…For example, a softer substrate could favour mud entrainment and fractionation and result in the deposition of a turbidite (cf. Baas et al, 2016). Although in principle this mechanism could work, it appears unlikely to be significant.…”
Section: Mud Volume Flow Behaviour and Depositional Processesmentioning
confidence: 97%
“…Lowe & Guy (2000) proposed a model of cyclic freezing of a near-bed plug flow, and postulate that banding forms between turbulent and laminar flow states, through variations in near-bed clay content modifying flow cohesion from low (sands-silt bands) to high (clayrich bands). However, flume tank experiments suggest flows with migrating bedforms within the upper stage plane bed flow regime can also produce banded beds (see Baas et al 2011;Baas et al 2016). Description: This facies comprises of dm-scale bipartite beds with lower fine-to medium-grained sandstone divisions, and upper argillaceous sandstone division (Fig.…”
Section: Transitional Flow Depositsmentioning
confidence: 99%